Ethical aspects of human biobanks: a systematic review - Budimir, Danijela (Croatian Medical Schools, 2011)
AIM: To systematically assess the existing literature on ethical aspects of human biobanks. METHOD: We searched the Web of Science and PubMed databases to find studies addressing ethical problems in biobanks with no limits set (study design, study population, time period, or language of publication). All identified articles published until November 2010 were included. We analyzed the type of published articles, journals publishing them, involvement of countries/institutions, year of publication, and citations received, and qualitatively assessed every article in order to identify ethical issues addressed by the majority of published research on human biobanking. RESULTS: Hundred and fifty four studies satisfied our review criteria. The studies mainly came from highly developed countries and were all published in the last two decades, with over half of them published in 2009 or 2010. They most commonly discussed the informed consent, privacy and identifiability, return of results to participants, importance of public trust, involvement of children, commercialization, the role of ethics boards, international data exchange, ownership of samples, and benefit sharing. CONCLUSIONS: The focus on ethical aspects is strongly present through the whole biobanking research field. Although there is a consensus on the old and most typical ethical issues, with further development of the field and increasingly complex structure of human biobanks, these issues will likely continue to arise and accumulate, hence requiring constant re-appraisal and continuing discussion.